PERANAN BADAN USAHA MILIK DESA (BUMDes) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA (Studi Kasus Pada Bumdes Cibokormas Desa Cibarani Kecamatan Cisata Kabupaten Pandeglang) - sujana, endang; Jumanah (NIAGARA Scientific Journal, 2024)
Village-Owned Enterprises (BUMDes) are village business institutions managed by the community and village government in an effort to strengthen the village economy which is formed based on community needs and village potential. However, in fact the formation of BUMDes in Cibarani Village has not been able to improve the economy of the people of Cibarani Village, Cisata District. There are various obstacles experienced in managing BUMDes. This research uses a qualitative method with a case study approach which reveals problems in the BUMDes management system in Cibarani Village, Cisata District. To make it easier to analyze the problem, it is analyzed using the theory regarding the BUMDes management system based on research results from the Center for Development System Dynamics Studies (PKSP) Brawijaya University (2017: 13). he results of the research found that the role of BUMDes in improving the economy of village communities was not optimal and Cibokormas BUMDes had not fully implemented the principles in managing BUMDes, there were obstacles or constraints, one of which was low community participation, low levels of trust, low quality human resources, and insufficient business capital. minimal. Various efforts have been made but have not been able to bring about business development and have not been able to strengthen the economy of Cibarani Village. Keywords: Role, BUMDes, Community economy.